Study of Dehumidification-regeneration Performance of an Internally-heating Regenerated Dehumidifier - L; Ning; Zhang Hui (Zhileng xuebao)
An internally-heating regenerated dehumidifier is proposed, its physical model and mathematical model for heat and mass transfer process are described, and a numerical procedure based on finite difference method is developed to solve the governing equations. By conducting experiment researches, the dehumidifier’s dynamic behavior is measured, and then compared with simulation data. Result shows that the dehumidifier has a high dehumidification efficiency for both indoor air with high moisture content in summer and relatively dry air in microenvironment without inner-cooling device, the time consumed in regeneration and cooling process is much less than that consumed in dehumidification process, and the pressure drop in fix bed is small, which indicates that the dehumidifier can be widely used in dehumidification for small indoor space.